Performance of Five Introduced Cabbage Varieties (Brassica oleracea var. capitata L.) Planted at the Highland of Pemalang Regency - Muntazul Ghiffar Hafidho; Rostaman Rostaman; Nurchasanah Siti; Faris Syaukany Rizza; Manoworn Chaiwat (E3S Web of Conferences)
Cabbage productivity in Indonesia has yet to reach its full potential, making the introduction of new cabbage varieties crucial to identifying those with specific advantages. This research aims to: (1) evaluate the adaptability of introduced cabbage varieties cultivated during the rainy season in Pemalang Regency, (2) compare genetic and phenotypic variations among these varieties, and (3) determine the heritability of key traits. The research was conducted in Gombong Village, Belik District, Pemalang Regency, at an altitude of 1100 meters above sea level on andosol soil from February 2023 to August 2024. Five introduced cabbage varieties—Omphalos, Tropicana, Kaelo, Saint, and Dolares—were tested, alongside comparison varieties Grand 11/Kubindo-1 and Green Nova. A randomized block design (RBD) was used, and quantitative data were analyzed with an F test (ANOVA) at a 5% error level, followed by a Dunnet test and genetic and phenotypic diversity estimates. Qualitative data were analyzed according to UPOV 2016 guidelines. Results showed that the introduced varieties had different adaptations, with high genetic diversity significantly influencing phenotypic traits. The heritability of each variety was relatively high, with genetic factors accounting for a larger share of variation in nine quantitative traits than environmental factors.